A study on the effect of occupational stress on job performance in the nursing staff of a tertiary care teaching hospital in Surendranagar district - Joshi, Krupal; Sochaliya, Kishor; Modi, Bhautik; Sharma, Lokesh; Singh, Snehil; Kartha, Girija P (Indian Journal of Community Health, 2021)
Introduction: Occupational stress is a health hazard to the individual worker both physically and psychologically. Research for the past years shows that, signs of occupational stress appear to be rising amongst nursing profession. The ability of nurses to appropriately handle stress while on duty may have a significant impact on individual outcomes, especially job performance. Objective: This study was conducted to measure the work-related stress and its association with the job performance among nurses. Methods: A pilot study was done and prevalence of work related stress was 13 % on the basis of which sample size was calculated which was 102 (in open epi). The 102 nurses were selected randomly from a tertiary care teaching hospital of Surendranagar district. The data was collected using a structured self-administered questionnaire which included questionnaires on demographic variables, level of work stress and job performance. Results: The findings of the study revealed that moderate and severe level of work stress was present in 53% and 45% of nurses respectively. The mean job stress score was found to be higher among younger nurses than those of more than 40 years. There was a negative relationship between job stress and job performance (r = ?0.01) among staff nurses. Conclusion: Based on study findings, it was concluded that all the nurses were suffering from mild to severe level of work stress. and it was negatively correlated with the job performance of the nurses. Hence, it is recommended that corrective measures may be planned by the authority to reduce the work stress of nurses to improve the job performance.